Demonstration of no catalytical activity of Fe‐N‐C and Nb‐N‐C electrocatalysts toward nitrogen reduction using in‐line quantification. Issue 4 (31st July 2022) - Sveinbjörnsson, Arnar; Gunnarsdóttir, Anna Bergljót; Creel, Erin B.; Canales, Camila Pía; Zulevi, Barr; Lyu, Xiang; Jafta, Charl J.; Skúlason, Egill; Serov, Alexey; Flosadóttir, Helga Dögg
Abstract: Ammonia (NH3 ) production via the electrochemical nitrogen reduction reaction (NRR) is a promising method for sustainable generation of this important chemical. Efforts are ongoing in finding an efficient, stable, and selective catalyst that will enable the reaction. However, progress is hindered in the field due to lack of reproducibility, most likely a consequence of reports of false‐positive results due to improper measurement control and methods. In this study, we explore the NRR activity of a promising class of single atom catalysts, transition metal‐nitrogen‐carbon (M‐N‐C) electrocatalysts. Using a state‐of‐the‐art in‐line ammonia quantification methodology, with detection limit as low as 1 ppb for ammonia, we show that single atom Nb and Fe embedded in a stable carbon and nitrogen framework do not electrochemically reduce N2 to NH3 . Critically, this demonstrates that our experimental setup with in‐line sequential injection analysis successfully excludes ammonia contamination from the gas supply and atmospheric sources, allowing for thorough and high‐throughput examination of potential NRR catalysts. Abstract :